The Financial-Economic Aspect of the Media and the Public Service in the Globalization Era (Budget and Ownership Framework) - Zeljko Rutovic (Journal of Central Banking Theory and Practice, 2017)
This study deals with influence of globalization on the economic aspect of the media. Financing the media and the issue of ownership over them represents the fundamental framework on which basis the media work and direct their editorial policy. Principle position implies that owners of the media use power of media to promote their economic, political, cultural and other stances. A particular issue, especially in European countries in transition, represents the financing of public service, as a socially beneficial good. Many commercial media, on the basis of their financial and political power, are trying to diminish or discredit the power and role of the public service. Former socialist countries, now countries in transition, seek from their national budgets to maintain this kind of informing, that is, the public interest, education and promoting cultural values. The era of globalization brought, as one of its negative traits, the domination of profit over culture, education, and even over the right to have quality informing. So the mass media have become a sort of hostage of confrontation of different political and economic interests, which reflects on the quality of media content that strive towards sensationalism, advertocracy, tabloidization. Based on the case study of Montenegro, as a country in transition, the development of mass media is shown, including their financing, ownership structure, and profit.
Keywords: H10; E62; 330; Globalization; media; financing; ownership; public service; Montenegro.